2013
DOI: 10.1186/2049-3002-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complex I is essential to induce a Warburg profile in mitochondria-defective tumor cells

Abstract: BackgroundAerobic glycolysis, namely the Warburg effect, is the main hallmark of cancer cells. Mitochondrial respiratory dysfunction has been proposed to be one of the major causes for such glycolytic shift. This hypothesis has been revisited as tumors appear to undergo waves of gene regulation during progression, some of which rely on functional mitochondria. In this framework, the role of mitochondrial complex I is still debated, in particular with respect to the effect of mitochondrial DNA mutations in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 63 publications
5
77
0
2
Order By: Relevance
“…To our knowledge this is the first successful demonstration of allotopic expression of a mitochondrial gene in cells that are both null for a protein and homoplasmic for that mutation. Previously, the MT - ND1 gene was allotopically expressed in ND1 null cells, but these cells were not completely homoplasmic and the purpose of that study was to identify the role of ND1 in tumorigenisis rather than to establish the biochemical functionality of allotopically expressed ND1 (20). Our approach completely removes the ambiguity that might be caused by competing with either WT or mutant proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge this is the first successful demonstration of allotopic expression of a mitochondrial gene in cells that are both null for a protein and homoplasmic for that mutation. Previously, the MT - ND1 gene was allotopically expressed in ND1 null cells, but these cells were not completely homoplasmic and the purpose of that study was to identify the role of ND1 in tumorigenisis rather than to establish the biochemical functionality of allotopically expressed ND1 (20). Our approach completely removes the ambiguity that might be caused by competing with either WT or mutant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…ATP6 expression was also able to partially rescue mutant CHO cells (16) while exogenous ND4 expression has been claimed to rescue rodent models of LHON (1719). Mutant MT-ND1 cells (OST-93 ND1 cells) were complemented by allotopic expression of ND1 with dramatic changes in the bioenergetics state and tumorgenic potential of the mutant cells (20). These cells are not perfectly homoplasmic (reported to carry a 93% mutation load) though the authors showed that this mutation load was sufficient to induce a null phenotype for the ND1 protein (21).…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis by Larman et al showed that, across 5 different cancer types, displayed somatic mtDNA mutations ranging, from 13% in glioblastoma to 63% frequency in rectal adenocarcinomas [133]. Some data suggests that the effect of the somatic mtDNA mutations and the degree or nature of the tumorigenesis effect depend on the functional and threshold effect of the mutation [134][135][136]. For instance, the m.3460G>A/MT-ND1 mutation (decrease in complex I activity) result in different tumorigenic potential as determined by colony forming efficiency and tumor growth of osteosarcoma cybrids (cytoplasmic hybrids, Fig.…”
Section: Somatic Mtdna Mutations Related To Cancermentioning
confidence: 99%
“…1114 Many experimental approaches have been proposed. 1517 However, only the allotopic expression approach 1827 has reached human testing in China (NCT01267422) and France (NCT02064569). We describe the preliminary findings from the first 5 participants enrolled in this trial based in the United States (NCT02161380).…”
mentioning
confidence: 99%